2016
DOI: 10.3402/qhw.v11.32488
|View full text |Cite
|
Sign up to set email alerts
|

Returning to work: The cancer survivor’s transformational journey of adjustment and coping

Abstract: The aim of this study was to explore cancer survivors’ return to work (RTW) experience with a specific focus on the adjustment and coping process underlying their journey. The study was conducted in the Southern Cape, South Africa, with eight cancer survivors having returned to work following successful treatment of various types of cancer. Unstructured interviews were conducted and data were analysed following the principles of hermeneutic phenomenological reflection and analysis. Four themes emerged, represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 54 publications
1
22
0
2
Order By: Relevance
“…When back at work, cancer patients often have to cope with declined physical and cognitive capacity, emotional concerns, self-confidence issues, a limited understanding of the effects of cancer by colleagues and employers and sometimes changes in the work environment. 17,18 Return to work (RTW) might therefore be seen as a process rather than a state, with healthrelated work functioning (hereafter referred to as work functioning) as a highly valuable outcome. Work functioning moves beyond employment status as it provides detailed information about experienced difficulties in meeting the demands of work given a health status.…”
mentioning
confidence: 99%
“…When back at work, cancer patients often have to cope with declined physical and cognitive capacity, emotional concerns, self-confidence issues, a limited understanding of the effects of cancer by colleagues and employers and sometimes changes in the work environment. 17,18 Return to work (RTW) might therefore be seen as a process rather than a state, with healthrelated work functioning (hereafter referred to as work functioning) as a highly valuable outcome. Work functioning moves beyond employment status as it provides detailed information about experienced difficulties in meeting the demands of work given a health status.…”
mentioning
confidence: 99%
“…Previous studies have also shown that conscientiousness and neuroticism were associated with a longer duration of unemployment and non‐RTW for healthy individuals . However, personality traits probably not only affect patients' RTW but also influence their coping efforts . A specific aspect of coping and positive reappraisal, akin to the concept of benefit finding, remains also to be investigated.…”
Section: Commentarymentioning
confidence: 99%
“…A specific aspect of coping and positive reappraisal, akin to the concept of benefit finding, remains also to be investigated. The qualitative study conducted by Barnard et al concluded that coping becomes constructive for RTW when a cancer survivor resolves to reassess his/her life and self through meaning‐making . This results in a renewed appreciation of life, appropriate lifestyle changes, and regained confidence in one's relational role .…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…This social cognitive model of restorative well-being was one of Lent's (Lent, 2004) two models of subjective well-being (SWB), which aimed at how people restore emotional equilibrium when confronted with particularly stressful conditions. Cancer is documented as a traumatic and life-changing event (Smith, Klassen, Coa, & Hannum, 2016) that results in a chronic condition (Ellis et al, 2017;Hoffman, Lent, & Raque-Bogdan, 2013) to which cancer survivors have to make adjustments and find ways of coping (Barnard, Clur, & Joubert, 2016). Because Hoffman and colleagues conceptually extended Lent's restorative well-being model to cancer coping (Hoffman et al, 2013), we see the model as having a particular utility for enhancing our understanding of the psychological adjustment mechanisms that cancer survivors' use as a basis for optimising their coping and for building well-being interventions.…”
Section: Introductionmentioning
confidence: 99%